2012
DOI: 10.1152/ajpgi.00366.2012
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 activation in mouse submandibular gland modulates Ca2+influx and salivation

Abstract: Zhang Y, Catalán MA, Melvin JE. TRPV4 activation in mouse submandibular gland modulates Ca 2ϩ influx and salivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…However, to our surprise, we did not detect saliva or tear secretion upon stimulation of salivary glands and LGs with a selective TRPV4 agonist alone (Supplemental Fig. 6), which is in contrast to a report by Zhang et al (30) showing that TRPV4 activation by GSK elicited saliva secretion in an ex vivo assay. Although the reason for this discrepancy is unclear, differences in experimental conditions could account in part for the different outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, to our surprise, we did not detect saliva or tear secretion upon stimulation of salivary glands and LGs with a selective TRPV4 agonist alone (Supplemental Fig. 6), which is in contrast to a report by Zhang et al (30) showing that TRPV4 activation by GSK elicited saliva secretion in an ex vivo assay. Although the reason for this discrepancy is unclear, differences in experimental conditions could account in part for the different outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports suggested that TRPV4 is involved in the regulatory volume decrease process in salivary glands and stimulates saliva secretion (29, 30). We first determined whether TRPV4 stimulation was sufficient to induce saliva and tear secretion in ex vivo and in vivo tissues from mice and found that GSK application alone did not promote fluid secretion from either SMG or LG (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations